Lissos in Illyria, 2 : A Hellenistic Fill from the Upper Town and Some Considerations on the Importance of Ceramic Debris - Kögler, Patricia (Journal of Hellenistic Pottery and Material Culture, 2021)
Extensive filling layers consisting of ceramic and other debris are a category of material that has been largely neglected in archaeological research and scientific evaluation. In the context of excavations, attention is usually only paid to the most recent pieces within such assemblages, as they may provide a terminus post quem for the settlement layers and building structures to be found above. Accordingly, the documentation and publication of filling layers – if it takes place at all – is usually selective and limited to dating material and uncommon finds.